The Role of Combination of 20% Azelaic Acid with 0.05% Tretinoin Cream in the Treatment of Melasma (Bangladesh Medical Journal, 2014)
Melasma is characterized by brown patches, typically on malar prominences and forehead. The pigmented patches are usually affect darker complexioned individual especially Asian. So it is a great problem in our country. A clinical trial was conducted to find out the effect of the combination of 20% azelaic acid cream with 0.05% tretinoin cream in the treatment of melasma. Thirty clinically diagnosed cases of melasma attending the outpatient department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, were enrolled Majority of !he study subjects (43%) were between 26 to 30 years and most of them (73.3%) were female. Regarding occupation 56.7% were housewife. Out of the study subjects 70% were married and 86.7% were of middle class. Around 66.7% cases had positive family history of melasma and maximum 93.3% patient had no history of systemic drug and the maxim11m 73.3% patient had no history of use of cosmetics. It was observed that highest (93.3%) number of patients had malar area involvement and 6. 7% had centro-facial area involvement. The st11dy showed that after treatment, the average MASI (Melasma Area and Severity Index) score was decreased by 38 66% indicating moderate reduction of the severity of melasma Out of the study subjects, 50%, 30%, 16% developed burning sensation, itching and erythema respectively It could be concluded that combination of 20% azelaic acid and 0.05% tretinoin cream, has a moderate lightening effect in the treatment of melasma. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18501 Bangladesh Medical Journal 2011 Vol.40(2): 26-30